Effect of Benson’s relaxation training on fatigue and sleep quality of elderly patients after surgery for with glioma (本森放松训练对老年胶质瘤术后患者疲乏程度与睡眠质量的影响) - GAO Yan (高严); HUANG Na (黄娜); DENG Lan (邓岚) (中西医结合护理)
Objective Using Benson’s relaxation training to reduce the physical tension and anxiety of elderly patients with glioma after surgery, improve the quality of sleep, relieve fatigue, and improve the satisfaction of patients during hospitalization. Methods A total of 100 elderly glioma patients admitted to the hospital from April to October 2022 were studied. They were randomly divided into observation group and control group, with 50 cases in each group. The control group received routine nursing measures, and the observation group was given Benson’s relaxation training on the basis of postoperative routine care. After 4 weeks, the Pittsburgh Sleep Quality Index (PSQI), revised-Piper Fatigue Scale (PFS-R) and patient nursing satisfaction were compared between the two groups. Results After 4 weeks of intervention, total score of PSQI and R-PFS in the observation group was lower than that in the control group respectively(P＜0. 01). The score of patient satisfaction in the observation group was lower than that in the control group(P＜0. 01). Conclusion Benson’s relaxation training can effectively improve the sleep quality of elderly glioma patients, reduce the degree of fatigue, improve nursing satisfaction. (目的 通过采用本森放松训练来缓解老年胶质瘤患者术后躯体紧张和焦虑感, 改善患者睡眠质量, 缓解疲乏, 提高患者住院期间的满意度。方法 选取2022年4月—10月首都医科大学附属北京天坛医院神经外科肿瘤六病区收治的100例老年胶质瘤患者为研究对象, 随机分为观察组和对照组, 各50例。对照组接受常规护理, 观察组在常规护理的基础上给予患者本森放松训练。干预4周后比较两组患者匹兹堡睡眠质量指数(PSQI)和Piper疲乏修订量表(PFS-R)评分, 评价患者护理满意度。结果 干预 4 周后, 观察组PSQI量表总分和R-PFS量表总分低于对照组, 差异有统计学意义(P＜0. 01)。观察组满意度评分高于对照组, 差异有统计学意义(P＜0. 01)。结论 本森放松训练方法能有效改善老年脑胶质瘤患者的睡眠质量, 降低患者疲乏程度, 提高护理满意度。)